EFFECT OF GAS ENRICHMENT AND FOLIAR WITH ORGANIC NUTRIENTS ON YIELD QUALITY OF BROCCOLI UNDER HYDROPONIC SYSTEM - A. D. Salman; I. J. Abdulrasool (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
A hydroponic experiment was carried out at the College of Agricultural Engineering Sciences - University of Baghdad during the fall season of 2019-2020 in order to improve the quality traits of broccoli grown hydroponically under the modified Nutrient Film Technique (NFT), using an internationally approved standard solution and alternative solution, the plant was enriched with ozone and the foliar application of organic nutrients. The Hydroponic study included two experiments with the standard solution (Cooper’s solution) and the alternative solution (ABEER). Both experiments were implemented within the Nested Design with three replications, and both included the gas type in the main plot, which were oxygen and ozone, while the sub-plot occupied with the foliar application of organic nutrients. The foliar application included the coconut water with two concentrations of 50 and 100 ml. L-1 and moringa leaves extract with two concentrations of 2 and 4%, in addition to the control treatment. Results were revealed a significant effect of ozone enrichment and the foliar application of coconut water at a concentration of 100 ml L-1 in the standard and alternative solutions, as the chlorophyl content (41.34, and 51.59%) and the β-Carotene (37.35 and 27.78 %) respectively. While the treatment of ozone enrichment and the foliar application of moringa leaves extract 2% for both solutions recorded the highest percentage Indol-3-Carbinol (54.03 and 56.40%) and Sulforaphane (51.66 and 43.95 mg kg dry weight-1) in the main heads respectively.